A Beethoven Sonata - Bergmüller, Karl Wilhelm, 1864-1928 (artist):::Creator:::::::::::: (Etude Magazine)
Color reproduction from an oil painting by C.W. Bergmüller, courtesy of Illustrirte Zeiting, Leipzig.